AN ANALYSIS OF STUDENTS-EDUCATOR’S POLITENESS STRATEGY TOWARD ONLINE COMMUNICATION IN EFL CONTEXT - Luh Metri Sulistya Sudeni (Universitas Islam Lamongan, 2022)
The ease of online communication in the current era seems to still leave issue that really need to be considered. Politeness in communicating between educators and students in carrying out message activities is one of the essential issues to be discussed. The lack of politeness between teachers in communicating, the large possibility of free communication when carrying out online communication, and the low awareness of teachers in emphasizing the importance of politeness in communication are some of the main problems that need to be resolved. This study aims to analyze the use of politeness strategies in communication between educators and students in EFL and try to analyze deeper what types of strategies are used by teachers and students in communicating, the steps they take to online communication, and get to know deeper regarding to the importance of politeness in communication. This research uses library research method and case study method to analyze the data. In addition to obtaining data from previous research sources, the authors also obtained data from ELE Undiksha lecturers and students. The theory expressed by Brown and Levinson in 1987 is the theory that underlies the analysis of this data which is the analysis of politeness strategy in communicating. From the literature study and also the case study method used to analyze the findings, it was found that the politeness strategy was more widely used by students than teachers, this was related to social position and age. The strategies used are positive politeness and bald on-record which are mostly used by students. On the other hand, negative politeness and off-record strategies are mostly used by teachers. It was also found that students used politeness more than their teachers and from a cultural point of view, the social status that separates teachers and students in Indonesia demands being able to give respect to the educators.Keywords: Politeness strategies, online communication, EFL context